Olympic Games volunteering genesis - Oleksandr Tomenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to consider the development of volunteer activity in relation to the Olympic Games. Material & Methods: theoretical scientific works of domestic and foreign scientists on the development of volunteer activities regarding their participation in the Olympic Games are analyzed, considered the main legal documents relating to the Olympic sport. Results: Statistical indicators of participation of volunteers in the Winter and Summer Olympics Games are analyzed and presented. The role and significance of volunteers' activity in the organization and holding of the Olympic Games are revealed. Conclusion: evolution of the volunteer movement, with reference to the Olympic Games, originates from the first games that took place in 1896 in Athens. To date, volunteers are an integral part of the organization and holding of the Olympic Games, their activities help to solve a number of organizational issues, the creation of a corresponding atmosphere and image at a sporting event, largely determine the success of games.